Analytical Modeling of Eco-Friendly Concrete Blocks from Construction and Demolition Waste using ANSYS - Usha S; Dr. T. V Mallesh (International Journal of Engineering and Management Research, 2023)
This research underscores the feasibility of repurposing C&D waste, particularly old concrete, for both new construction endeavors and revamping existing projects. This approach offers a dual advantage: preserving precious landfill space while curbing the extraction of raw materials for fresh construction initiatives. Focusing on the utilization of demolished waste as partial replacements for coarse aggregates sourced from C&D Waste Traders in Sirjala, Bengaluru, 10 mm sized recycled aggregates are employed. Recognizing the porous nature of crushed aggregates owing to residual slurry, a meticulous treatment process is adopted. This includes two-stage treatment involving abrasion to eliminate residual loose slurry, followed by immersion in a fly ash solution with a concentration ratio of 1:6. Subsequently, these treated aggregates, after the curing process, are amalgamated with a robust geopolymer precursor in a mix ratio of 1:3:6 to fabricate 400X200X150 mm blocks. To gauge the masonry behavior of these innovative concrete blocks, a battery of tests conforming to ASTM codes is meticulously conducted. These evaluations serve as a robust assessment of the structural integrity, durability, and performance characteristics of the blocks, providing critical insights into their potential for widespread adoption in construction practices. This comprehensive analysis contributes to the growing body of knowledge on sustainable construction materials and practices, advocating for a paradigm shift towards eco-friendly construction methodologies amidst the burgeoning challenges of waste management and resource scarcity.